2021
DOI: 10.1038/s41433-021-01734-4
|View full text |Cite
|
Sign up to set email alerts
|

Endocyclophotocoagulation combined with phacoemulsification in surgically naive primary open-angle glaucoma: three-year results

Abstract: Objective To assess the safety and efficacy of endocyclophotocoagulation with phacoemulsification (phaco-ECP) in surgically naive, primary open-angle glaucoma (POAG). Methods A retrospective case series of patients undergoing phaco-ECP between 2007 and 2017 at a single centre in London, UK. The primary outcome was intraocular pressure (IOP). Secondary outcomes were visual acuity, visual field global indices, topical medications and surgical complications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
(43 reference statements)
0
2
0
1
Order By: Relevance
“… 19 The nature of complications in both MIGS groups was similar to that of other studies as complications were minimal in severity and self-limiting. 29 , 30 The most striking observation was the high rate of active inflammation beyond POM1 in the ECP group compared to the KDB group. A previous study reported that up to 24% of ECP cases could be complicated by protracted post-op inflammation.…”
Section: Discussionmentioning
confidence: 97%
“… 19 The nature of complications in both MIGS groups was similar to that of other studies as complications were minimal in severity and self-limiting. 29 , 30 The most striking observation was the high rate of active inflammation beyond POM1 in the ECP group compared to the KDB group. A previous study reported that up to 24% of ECP cases could be complicated by protracted post-op inflammation.…”
Section: Discussionmentioning
confidence: 97%
“…109 Yap et al assessed the 3-year outcomes of phaco/ECP in POAG eyes. 110 They reported success rates of 70%, 54%, and 45% at years 1, 2, and 3, respectively, with statistically significant reductions in mean IOP and the number of topical medications from preoperative levels (P < 0.0001). Similarly, a study by Lindfield et al showed that phaco/ECP resulted in a statistically significant reduction in IOP at all postoperative time points up to 24 months, with a mean decrease of 7.1 mm Hg.…”
Section: Endoscopic Cyclophotocoagulationmentioning
confidence: 93%
“…Previously used in refractory glaucoma, ECP is now utilized earlier in disease due to the advent of MIGS 109 . Yap et al assessed the 3-year outcomes of phaco/ECP in POAG eyes 110 . They reported success rates of 70%, 54%, and 45% at years 1, 2, and 3, respectively, with statistically significant reductions in mean IOP and the number of topical medications from preoperative levels ( P < 0.0001).…”
Section: Non-bleb Forming Inflow Reducing Approachesmentioning
confidence: 99%
“…1 Medikament (− 0,9 ± 1,5) berichtet. 25 % der Patienten waren nach 3 Jahren medikamentenfrei und ohne weitere Operation [24]. Prospektive Vergleichsstudien mit abflussverbessernden minimalinvasiven Eingriffen wären hier wünschenswert.…”
Section: Endo-zyklophotokoagulationunclassified